Ownership structure and financial reporting quality: Influence of audit quality evidence from Jordan - Wan Anisah, Endut; Nik Mohd Norfadzilah, Nik Mohd Rashid; Hamza Kamel, Qawqzeh (2019)
The issues of ownership structure, audit quality, earnings management and financial reporting quality have received more consideration from public, profession and other interested parties particularly after persistent firms' scandals. Ownership structure play essential role in improve financial reporting quality (FRQ) through acting as effective internal control. This study examines the influence of the various types of ownership on the FRQ and the influence of audit quality. A stream of literature has examined the relationships between the different types of ownership, audit quality and FRQ. This study aims to connect such of these variables to produce an integrated model describing the influence of ownership structure with in the company and audit quality on FRQ. Therefore, the following relationships are tested: Ownership structure and FRQ, Mediating effect of auditor quality on these relationships, and audit quality and FRQ. Using Panel Data of 180 Jordanian company listed in ASE from 2009-2017, results showed that directors' and family ownership have significantly positive effect on FRQ through reducing earnings management; Institutional ownership has significantly negative influence on FRQ; Managerial ownership has insignificant impact on FRQ. Audit quality has partial mediating impact on these relationships. Audit quality found to has significantly positive impact on FRQ, it implies that audit quality is considered as deterrent to earnings management. This study suggests to increase the supervisory and monitoring role of institutional ownership on the management when preparing financial statements.